The Mediating Effect of HRM Practices on the Relationship Between Business Strategy and Employee Outcomes - Koon, Vui Yee; Juhary, Ali (AeU, 2015)
This study examines the effects of human resource management (HRM) practices on strategic approach on employee attitudes and behaviors in Public and Private limited companies in Malaysia. Specifically, the study examines the combination effect of HRM practices variable of the relationship between business strategy of the company and employee outcomes such as organizational commitment, job satisfaction, employee involvement and employee turnover. The framework is tested using structural equation modeling and the data are from 571 non-human resource department employees from two different types of business ownership in Malaysia. The hypothesized relationship is tested using AMOS 16.0 through path analysis. The results of the confirmatory factor analysis demonstrated relatively a reasonable fit of the model to the data on the basis of a number of fit statistics (χ2= 1184.856; GFI (goodness-of-fit index) = 0.903; CFI (comparative fit index) = 0.927; TLI (Tucker-Lewis index) = 0.918 and RMSEA (root mean square error of approximation) = 0.037). This study found the mediation effect of HRM practices between business strategy and employee outcomes showed mixed results.